Monoquaternary pyridinium salts with modified side chain-synthesis and evaluation on model of tabun- and paraoxon-inhibited acetylcholinesterase - Musilek, Kamil; Kucera, Jiri; Jun, Daniel; Dohnal, Vlastimil; Opletalova, Veronika; Kuca, Kamil (Bioorganic & medicinal chemistry, 2008)
Acetylcholinesterase reactivators are crucial antidotes for the treatment of organophosphate intoxication. Eighteen monoquaternary reactivators of acetylcholinesterase with modified side chain were developed in an effort to extend the properties of pralidoxime. The known reactivators (pralidoxime, HI-6, obidoxime, trimedoxime, methoxime) and the prepared compounds were tested in vitro on a model of tabun- and paraoxon-inhibited AChE. Monoquaternary reactivators were not able to exceed the best known compounds for tabun poisoning, but some of them did show reactivation better or comparable with pralidoxime for paraoxon poisoning. However, extensive differences were found by a SAR study for various side chains on the non-oxime part of the reactivator molecule.
Keywords: Cholinesterase Inhibitors; Enzyme Activation; preklinické hodnocení léčiv; Structure-Activity Relationship; Brain; molekulární struktura; Molecular Structure; racionální návrh léčiv; Paraoxon; vztah mezi dávkou a účinkem léčiva; Models, Biological; acetylcholinesterasa; Pyridinium Compounds; vztahy mezi strukturou a aktivitou; krysa rodu Rattus; organofosfáty; stereoizomerie; Animals; pyridinové sloučeniny; biologické modely; aktivátory enzymů; zvířata; Drug Evaluation, Preclinical; Rats; mozek; aktivace enzymů; Drug Design; Enzyme Activators; Acetylcholinesterase; cholinesterasové inhibitory; paraoxon; Dose-Response Relationship, Drug; Organophosphates; Stereoisomerism